Million flickering embers : a multidisciplinary analysis of child mortality in Uganda - Tindifa, Samuel B. (Sam) (University of Pretoria, 2012)
Thesis (LLM (Human Rights and Democratisation in Africa))--University of Pretoria, 2012.